Planning Lessons and Courses:designing sequences of work for the language classroom - Woodward, Tessa (UK. : Cambridge University Press, 2001)
Language and Literature
Keywords: Planning Lessons and Courses; Students; Classroom; Lesson; who can teach; activities; preparation; Freedoms and Constraints